Effective protection of photoreceptors using an inflammation-responsive hydrogel to attenuate outer retinal degeneration - Hyerim Kim; Hyeonhee Roh; Sang-Heon Kim; Kangwon Lee; Maesoon Im; Seung Ja Oh (npj Regenerative Medicine, 2023)
Abstract Retinitis pigmentosa (RP) is an outer retinal degenerative disease that can lead to photoreceptor cell death and profound vision loss. Although effective regulation of intraretinal inflammation can slow down the progression of the disease, an efficient anti-inflammatory treatment strategy is still lacking. This study reports the fabrication of a hyaluronic acid-based inflammation-responsive hydrogel (IRH) and its epigenetic regulation effects on retinal degeneration. The injectable IRH was designed to respond to cathepsin overexpression in an inflammatory environment. The epigenetic drug, the enhancer of zeste homolog 2 (EZH2) inhibitors, was loaded into the hydrogel to attenuate inflammatory factors. On-demand anti-inflammatory effects of microglia cells via the drug-loaded IRH were verified in vitro and in vivo retinal degeneration 10 (rd10) mice model. Therefore, our IRH not only reduced intraretinal inflammation but also protected photoreceptors morphologically and functionally. Our results suggest the IRH reported here can be used to considerably delay vision loss caused by RP.